2015
DOI: 10.4236/ajibm.2015.512073
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Decision Making in Adopting E-Commerce between Indonesia and Chinese Taipei (Case Study in Jakarta and Taipei City)

Abstract: The number of people using internet has increased due to advances in information technology, and the growth of electronic commerce (e-commerce) is increasingly growing. This study aims to investigate the factors that influence consumer intention to adopt e-commerce in Jakarta and Taipei. In this paper, additional variables such as trust, costs, social influences, various services, and control variables such as age, educational level, and gender of consumers become work extension of traditional model of technol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 53 publications
0
1
0
1
Order By: Relevance
“…Dibutuhkan cara agar produk lokal juga dapat dipasarkan ke luar provinsi Banten, maupun ke mancanegara. Salah satunya adalah pemanfaatan digital marketing melalui, mesin pencari (google) ataupun media sosial (Chang Shia et al, 2015).…”
Section: Pendahuluanunclassified
“…Dibutuhkan cara agar produk lokal juga dapat dipasarkan ke luar provinsi Banten, maupun ke mancanegara. Salah satunya adalah pemanfaatan digital marketing melalui, mesin pencari (google) ataupun media sosial (Chang Shia et al, 2015).…”
Section: Pendahuluanunclassified
“…TAM was proposed by Fred Davis (1986) for his doctorate proposal . The theory posits that, consumers' behavioural intentions are influenced by their attitude towards technology adoption; which in turn is determined by two constructs namely: Perceived Usefulness (PU) and Perceived Ease of Use (PEOU) (Shia, et al, 2015). TAM postulates that these two beliefs (PU & PEOU) are of primary relevance to evaluate E-Commerce acceptance behaviours (Davis, et al, 1989).…”
Section: Technology Adoption Modelmentioning
confidence: 99%
“…It refers to the extent to which individuals can try and experience digital banking services before fully committing to them or conduct tests with a new piece of technology before it is officially adopted. Research has consistently shown that trialability positively impacts the adoption of digital banking services (Pobee, 2021;Shia et al, 2015).…”
Section: The Relationship Between Trialability and Adoption Of Digita...mentioning
confidence: 99%
“…Moreover, trialability enhances a customer's perceived usefulness of digital banking services (Yoon & Lim, 2020). Furthermore, trialability also reduces the uncertainty and risk associated with adopting digital banking services (Shia et al, 2015). When individuals can experience the benefits and convenience of digital banking services through trialability, they are likely to adopt and use these services in the long run (Haider & Akram, 2017).…”
Section: The Relationship Between Trialability and Adoption Of Digita...mentioning
confidence: 99%